(untitled) (Memoria y Civilización, 2003)
Remembered as a liberal man, brilliant pioneer in investigation of the social history of mentalities, José Antonio Maravall was, nevertheless, one of the main teachers and moving forces of the post war falangism. This is to say, of the Falangist project supported by the power of Ramón Serrano Súñer as the brother in law of Francisco Franco and as the Minister of Government and Overseas Affairs. A project which Maravall himself identifed with the European totalitarian movement represented, essentially, by Nazi Germany and which he defended as the best option for social and political reconstruction of the Spain resulting from the civil war.